The impact of verbal encouragement during the repeated agility speed training on internal intensity, mood state, and physical enjoyment in youth soccer players - Selmi, Okba; Jelleli, Hilmi; Bouali, Souheir; Aydi, Bilel; Hindawi, Omar; Muscella, Antonella; Bouassida, Anissa; Weiss, Katja; Knechtle, Beat (Frontiers in Psychology, 2023)
Objective: Verbal encouragement (VE) can be used by coaches to boost morale and commitment during training exercises. This investigation aimed to study the impacts of VE given by coaches on the physiological aspects, players' internal intensity, mood, and perceived enjoyment of youth soccer players during repeated agility speed training (RAS).Methods: Seventeen male youth soccer players (Mean ± SD: age: 13.8 ± 0.4 years; body mass: 59.1 ± 6.7 kg; height: 170.0 ± 6.2 cm; training experience: 5.1 ± 0.7 years) performed, in a randomized order, two experimental training that consisted a RAS (i.e., the Illinois course) either with VE (RAS-E) or without VE (RAS-NE), with seven days interval between the testing sessions. Heart rate (HR) was registered throughout the exercise. The rating of perceived exertion (RPE), blood lactate concentration [La], and perceived enjoyment was measured after each training session. The mood state was recorded pre and post each protocol.Results: HR mean (Cohen's coefficient d = 0.45, small), %HRmax (d = 0.37, small), HR peak (d = 0.66, moderate), [La] (d = 0.56, small) and the PACES score (d = 2.8, very large) were higher in RAS-E compared to RAS-NE (all, P<0.001). Compared to the RAS-E trial, the RAS-NE trial showed higher fatigue (P<0.01), tension (P<0.05), anger (0.05), total mood score (TMD) (P<0.001), and a lower vigor (P<0.001).Coaches may use VE during RAS to improve psychophysiological responses, mood state and perceived enjoyment in youth soccer players.